Testing Reciprocal Associations between Parenting and Youth's Motivational Resources of Career Decision-Making Agency during the Postsecondary Transition. - Ahn, Jiseul Sophia; Ratelle, Catherine F.; Plamondon, André; Duchesne, Stéphane; Guay, Frédéric (Journal of Youth & Adolescence, 2022)
Parents are central figures in youth's career decision-making processes. One of their key roles is to foster youth's career decision-making agency by supporting their motivational resources—of autonomy and competence. While the findings on parent-driven effects (how parenting behaviors predict youth's agency) are well documented, little is known about the opposite direction—child-driven effects (how youth's agency predicts parenting behaviors)—and the bidirectionality, particularly during postsecondary transitions. To address this gap, the current study examined (1) reciprocal linkages between mothers' and fathers' parenting behaviors (i.e., need support and control) and youth's agency (i.e., autonomy and competence) and (2) whether such linkages are moderated by the parent's gender and timing. Participants were 642 French-Canadian youths (54% girls; M = 14.2) who annually reported on parenting behaviors and career decision-making agency for 5 years, from Secondary 3 to 2 years postsecondary. For analysis, random-intercept cross-lagged panel models were estimated to disentangle the between- and within-family processes. The results showed that youth's career decision-making competence develops in reciprocal transactions with parental need support in an upward spiral, while autonomy development is primarily driven by need support. Limited evidence was found for the moderating effects of parents' gender and youth's transition periods. Preregistration: the present study was preregistered (the study design, hypotheses, and target analyses). The preregistration can be found in https://osf.io/c5hak. Any deviations from the preregistration can be found in the Online Supplemental Materials.